2020
DOI: 10.1101/2020.05.27.118752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 envelope protein topology in eukaryotic membranes

Abstract: Coronavirus E protein is a small membrane protein found in the virus envelope. Different coronavirus E proteins share striking biochemical and functional similarities, but sequence conservation is limited. In this report, we studied the E protein topology from the new SARS-CoV-2 virus both in microsomal membranes and in mammalian cells. Experimental data reveal that E protein is a single-spanning membrane protein with the N-terminus being translocated across the membrane, while the C-terminus is exposed to the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The exact function of the N‐terminus of the E protein has not been clearly identified. This region is located inside the Golgi/ER membrane, and Asn15 in the domain forms an H‐bond, which maintains the stability of the N‐terminus 57,58 . Studies have shown that homotypic interactions mediated by the N‐terminus of alternating E protein molecules may interact with each other through the luminal loops between the TMD of the proteins to initiate the rearrangement of ER membranes and induce membrane curvature.…”
Section: Differences In Amino Acid Sequence and Structure Between The Sars‐cov And Sars‐cov‐2 E Proteinsmentioning
confidence: 99%
“…The exact function of the N‐terminus of the E protein has not been clearly identified. This region is located inside the Golgi/ER membrane, and Asn15 in the domain forms an H‐bond, which maintains the stability of the N‐terminus 57,58 . Studies have shown that homotypic interactions mediated by the N‐terminus of alternating E protein molecules may interact with each other through the luminal loops between the TMD of the proteins to initiate the rearrangement of ER membranes and induce membrane curvature.…”
Section: Differences In Amino Acid Sequence and Structure Between The Sars‐cov And Sars‐cov‐2 E Proteinsmentioning
confidence: 99%
“…An even-net charge distribution was discovered on both sides of the E-protein membrane. Only eight charged residues have been discovered in the protein sequence: two negatively charged residues preceding the transmembrane section, five charged residues, and one negatively charged residue in the C-terminal domain [ 17 ]. Interestingly during the replication cycle, only a few portions are assimilated into the virion envelope, and on the contrary, the protein is mostly expressed inside the infected cell [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…After a short centrifugation (1000 rpm for 5 min on a table-top centrifuge) cells were lysed by adding 100 μL of lysis buffer (30 mM Tris-HCl, 150 mM NaCl, 0.5% Nonidet P-40) were sonicated in an ice bath in a bioruptor (Diagenode) during 10min and centrifuged. After protein quantification, equal amounts of protein were submitted to Endo H treatment or mock-treated followed by SDS-PAGE analysis and transferred into a PVDF transfer membrane (ThermoFisher Scientific) as previously described [40]. Protein glycosylation status was analysed by Western Blot using an anti-c-myc antibody (Sigma), anti-rabbit IgG-peroxidase conjugated (Sigma), and with ECL developing reagent (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%